SEDIMENT TRANSPORT TIME MEASURED WITH U-SERIES ISOTOPES: RESULTS FROM ODP NORTH ATLANTIC DRIFT SITE 984 - DePaolo D.J.; Maher K.; Christensen J.N.; McManus J. (My University, 2006)
High precision uranium isotope measurements of marine clastic sediments are used to measure the transport and storage time of sediment from source to site of deposition. The approach is demonstrated on fine-grained, late Pleistocene deep-sea sediments from Ocean Drilling Program Site 984A on the Bjorn Drift in the North Atlantic. The sediments are siliciclastic with up to 30% carbonate, and dated by δ18O of benthic foraminifera. Nd and Sr isotopes indicate that provenance has oscillated between a proximal source during the last three interglacial periods - volcanic rocks from Iceland - and a distal continental source during glacial periods. An unexpected finding is that the 234U/238U ratios of the silicate portion of the sediment, isolated by leaching with hydrochloric acid, are significantly less than the secular equilibrium value and show large and systematic variations that are correlated with glacial cycles and sediment provenance. The 234U depletions are inferred to be due to α-recoil loss of 234Th, and are used to calculate "comminution ages" of the sediment - the time elapsed between the generation of the small (≤ 50 μm) sediment grains in the source areas by comminution of bedrock, and the time of deposition on the seafloor. Transport times, the difference between comminution ages and depositional ages, vary from less than 10 ky to about 300 to 400 ky for the Site 984A sediments. Long transport times may reflect prior storage in soils, on continental shelves, or elsewhere on the seafloor. Transport time may also be a measure of bottom current strength. During the most recent interglacial periods the detritus from distal continental sources is diluted with sediment from Iceland that is rapidly transported to the site of deposition. The comminution age approach could be used to date Quaternary non-marine sediments, soils, and atmospheric dust, and may be enhanced by concomitant measurement of 226Ra/230Th, 230Th/234U, and cosmogenic nuclides. © 2006 Elsevier B.V. All rights reserved.
Keywords: GEOCHRONOLOGY; GLACIAL CYCLES; ISOTOPE GEOCHEMISTRY; NORTH ATLANTIC; SEDIMENT TRANSPORT; U-SERIES ISOTOPES; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Quaternary::Pleistocene